Novel Aminoguanidine Hydrazone Analogues: From Potential Antimicrobial Agents to Potent Cholinesterase Inhibitors - Krátký, Martin; Štěpánková, Šárka; Konečná, Klára; Svrčková, Katarína; Maixnerová, Jana; Švarcová, Markéta; Janďourek, Ondřej; Trejtnar, František; Vinšová, Jarmila (My University, 2021)
Aseries of thirty-one hydrazones of aminoguanidine, nitroaminoguanidine, 1,3-diaminoguanidine, and (thio)semicarbazide were prepared from various aldehydes, mainly chlorobenzaldehydes, halogenated salicylaldehydes, 5-nitrofurfural, and isatin (yields of 50–99%). They were characterized by spectral methods. Primarily, they were designed and evaluated as potential broad-spectrum antimicrobial agents. The compounds were effective against Gram-positive bacteria including methicillin-resistant Staphylococcus aureus with minimum inhibitory concentrations (MIC) from 7.8 M, as well as Gram-negative strains with higher MIC. Antifungal evaluation against yeasts and Trichophyton mentagrophytes found MIC from 62.5 M. We also evaluated inhibition of acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE). The compounds inhibited both enzymes with IC50 values of 17.95–54.93 M for AChE and 1.69 M for BuChE. Based on the substitution, it is possible to modify selectivity for a particular cholinesterase as we obtained selective inhibitors of either AChE or BuChE, as well as balanced inhibitors. The compounds act via mixed-type inhibition. Their interactions with enzymes were studied by molecular docking. Cytotoxicity was assessed in HepG2 cells. The hydrazones differ in their toxicity (IC50 from 5.27 to >500 M). Some of the derivatives represent promising hits for further development. Based on the substitution pattern, it is possible to modulate bioactivity to the desired one.
Nové analogy aminoguanidinhydrazonu: od potenciálních antimikrobiálních látek k účinným inhibitorům cholinesterázy
Keywords: acetylcholinesterase; aminoguanidine; antimicrobial activity; butyrylcholinesterase; cytotoxicity; enzyme inhibition; hydrazones; molecular docking; salicylaldehydes; acetylcholinesteráza; aminoguanidin; antimikrobiální aktivita; butyrylcholinesteráza; cytotoxicita; inhibice enzymů; hydrazony; molekulární dokování; salicylaldehydy